Infrastructure Projects : A Review of Canceled Private Projects - Harris, Clive; Hodges, John; Schur, Michael (World Bank, Washington, DC, 2012)
In recent years the renegotiation and, even more, the cancellation of private infrastructure projects in developing countries have made the headlines in the world's financial press. For a variety of reasons the renegotiation of projects is not an unusual occurrence. But as this Note explains, only 48 private infrastructure projects in developing countries were canceled in 1990-2001, a small fraction of the nearly 2,500 projects that reached financial closure over this period. The note further explains the definition of cancellation, the reasons for cancellation, and expands on the implications for private provision of infrastructure.